Electro‐Mechanochemical Atom Transfer Radical Cyclizations using Piezoelectric BaTiO(3) - Schumacher, Christian (John Wiley and Sons Inc., 2020)

(untitled) (Angew Chem Int Ed Engl)
The formation and regeneration of active Cu(I) species is a fundamental mechanistic step in copper‐catalyzed atom transfer radical cyclizations (ATRC). Typically, the presence of the catalytically active Cu(I) species in the reaction mixture is secured by using high Cu(I) catalyst loadings or the addition of complementary reducing agents. In this study it is demonstrated how the piezoelectric properties of barium titanate (BaTiO(3)) can be harnessed by mechanical ball milling to induce electrical polarization in the strained piezomaterial. This strategy enables the conversion of mechanical energy into electrical energy, leading to the reduction of a Cu(II) precatalyst into the active Cu(I) species in copper‐catalyzed mechanochemical solvent‐free ATRC reactions.